2011
DOI: 10.1002/env.1031
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of different regression modelling strategies in epidemiology: a time-series analysis of hospital admissions and air pollutants in Lisbon (1999-2004)

Abstract: a Studies of the acute health effects of air pollution have used exposure windows of different spans and related them to single-day responses. Little is known about whether an increased response window span might be a viable alternative to single-day responses. Our aim is to compare a new model specification where both the exposure and response variables are represented as 7 day moving averages (CMA&CMA model) with the most widely used model specifications in the literature, where the response variable is usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…1). In HA database, it was observed that hospital admission counts tend to be lower on weekends as compared to working days, as already concluded by Sarmento et al (2009), suggesting that either weekend admissions are registered on Mondays only or patients wait for Monday to go to hospital if the symptoms are not so severe or the number of doctors in hospital is reduced during weekend and people may wait to Monday to be assisted. This is visible in Fig.…”
Section: Hospital Admissionsmentioning
confidence: 50%
See 3 more Smart Citations
“…1). In HA database, it was observed that hospital admission counts tend to be lower on weekends as compared to working days, as already concluded by Sarmento et al (2009), suggesting that either weekend admissions are registered on Mondays only or patients wait for Monday to go to hospital if the symptoms are not so severe or the number of doctors in hospital is reduced during weekend and people may wait to Monday to be assisted. This is visible in Fig.…”
Section: Hospital Admissionsmentioning
confidence: 50%
“…Studies on human health effects usually use daily data; although, recent epidemiological studies have been using exposures in the form of moving averages, distributed lags or data aggregated over several days or even weeks (Schwartz 2000b;Sarmento et al 2009). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, epidemiological associations between PM and health outcomes are based predominantly on ambient air measurements where it is assumed that each person in a given region has the same exposure level, which is often obtained from a few air quality monitors and reflects the entire community Freitas et al, 2009a,b;Sarmento et al, 2011). Nevertheless, poor correlations have been found between ambient PM concentrations and personal exposure to PM (Meng et al, 2005) because actual exposure is strongly related to the individual time activity patterns, followed by its distance from each particle source.…”
Section: Introductionmentioning
confidence: 99%